Stopping doctor-patient communication gap: The ten essential methods (2010)
Background : An effective doctor-patient communication has increasingly being recognized as an important factor in patient care. All means should be oriented towards narrowing communication gap. The essential methods must be searched and doctor must be able to conduct communication session in more pleasing manner. Methodology: This is a systematic review on observations made on doctor-patient relationship on various setting and supported by feedbacks from many scholars who are involved in research, teaching and also papers and studies on the said subject. Results: It is been realized that effective communication is not easily done if its process not well complemented and the gap is left widening. From all possible communication gaps recognized and listed, at least ten have identified to be the most essential methods to be prioritized while counselling or consulting a patient. Conclusion: Effective communication between patient and doctor is the essential prerequisite of good medical practice and especially important for accurate diagnosis and effective treatment. Its mutual benefit can only be observed if all efforts are centered towards managing the communication gap.